2022
DOI: 10.3390/horticulturae8121156
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Anatomical, Physiological and Biochemical Changes during Adventitious Roots Formation of Bougainvillea buttiana ‘Miss Manila’

Abstract: Bougainvillea, a widely used ornamental plant, is mainly propagated by cuttings and tissue culture. Still, large-scale production of Bougainvillea is often difficult because of rooting issues. Therefore, based on an early establishment of the regeneration system for tissue culture in Bougainvillea by our research team, we further studied its rooting mechanism. It was observed that the morphology and anatomical structure of Bougainvillea buttiana ‘Miss Manila’ contained endogenous hormones, such as indole-3-ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…It has been reported that there is a direct or indirect correlation between different endogenous hormones and antioxidant enzymes, as well as other physiological substances, which collectively affects differentiation and morphogenesis during tissue culture [33,34]. In this study, the correlation analysis showed that the activity of all three enzymes was positively correlated with the content of IAA and ABA while negatively correlated with the content of 6-BA, ZT, and GA 3 .…”
Section: Differences In the Endogenous Hormone Content And Antioxidan...mentioning
confidence: 51%
See 1 more Smart Citation
“…It has been reported that there is a direct or indirect correlation between different endogenous hormones and antioxidant enzymes, as well as other physiological substances, which collectively affects differentiation and morphogenesis during tissue culture [33,34]. In this study, the correlation analysis showed that the activity of all three enzymes was positively correlated with the content of IAA and ABA while negatively correlated with the content of 6-BA, ZT, and GA 3 .…”
Section: Differences In the Endogenous Hormone Content And Antioxidan...mentioning
confidence: 51%
“…Antioxidant enzymes can scavenge reactive oxygen species and lipid peroxidation products, and their activity is commonly enhanced when suffering from biotic or abiotic stresses [32]. Like excess PGRs, when under specific in vitro culture conditions, the in vitro cultures may suffer from oxidative stress and, consequently, will regulate the endogenous hormone content and antioxidant enzyme activity to alleviate oxidative damage [33,34]. Schnablova et al [35] reported that the overproduction of endogenous cytokinins increased the activity of some antioxidant enzymes involved in lignification, such as syringaldazine peroxidase and guaiacol peroxidase.…”
Section: Introductionmentioning
confidence: 99%
“…During plant cuttings, the ratio of endogenous hormone levels bears close relation with the formation of adventitious roots [58]. According to Quan et al [59], the higher the values of IAA/ABA and IAA/ZR are, the easier it is to form roots.…”
Section: Discussionmentioning
confidence: 99%
“…It is extensively cultivated in urban landscaping projects in tropical and subtropical regions due to its exceptional ornamental value and diverse potential applications. Bougainvillea has several garden advantages, including rapid growth, high organ differentiation [20], and easy reproduction [21,22]. In addition, in terms of ecological regulation, Bougainvillea has a certain tolerance and regulation ability to water bodies [23,24], air [7,25,26], and soil [27].…”
Section: Introductionmentioning
confidence: 99%